Optimising planned medical education strategies to develop learners' person-centredness: a realist review - Bansal, A; Greenley, S; Mitchell, C; Park, S; Shearn, K; Reeve, J (Wiley, 2021)
Context Person-centeredness is a stated aim for medical education; however, studies suggest this is not being achieved. There is a gap in our understanding of how, why and in what circumstances medical education interventions that aim to develop person-centredness are successful. Methods A realist review was conducted with a search of Medline, Embase, HMIC and ERIC databases and the grey literature using the terms ‘medical education’ and ‘person-centred’ and related synonyms. Studies that involved a planned educational intervention in medical education with data on outcomes related to person-centredness were included. The analysis focused on how and why different educational strategies interact with biomedical learner perspectives to trigger mechanisms that may or may not lead to a change in perspective towards person-centredness. Results Sixty-one papers representing fifty-three interventions were included in the final synthesis. Nine context–intervention–mechanism–outcome configuration (CIMOc) statements generated from the data synthesis make up our refined programme theory. Where educational interventions focused on communication skills learning or experiences without person-centred theory, learners experienced dissonance with their biomedical perspective which they resolved by minimising the importance of the learning, resulting in perspective endurance. Where educational interventions applied person-centred theory to meaningful experiences and included support for sense making, learners understood the relevance of person-centeredness and felt able to process their responses to learning, resulting in perspective transformation towards person-centredness. Conclusion Our findings offer explanations as to why communication skills-based interventions may be insufficient to develop learners' person-centredness. Integrating experiential person-centred learning with theory on why person-centredness matters to clinical practice and enabling learners to make sense of their responses to learning, may support perspective transformation towards person-centredness. Our findings offer programme and policymakers testable theory to inform the development of medical education strategies that aim to support person-centredness.